Performance Analysis of Regional Original Income in Maluku Province and its Optimization Strategy - Djufri Rays Pattilouw (SEAN Institute, 2023)
Regional autonomy on the one hand has had a positive impact in the form of opening opportunities for regions to regulate and manage the interests of local communities according to their own initiatives. However, on the other hand, regional autonomy also gave birth to a number of serious consequences, including the still high dependence of local government finances on the central government because the regional fiscal capacity has not been able to finance the growing demand for development needs in the regions. High regional fiscal dependence also occurs in Maluku Province, where the contribution of Local Own Revenue (PAD) to the total regional revenue of Maluku Province in 2018 is only 15.2 percent. This figure even decreased compared to previous years which averaged around 18 percent. Meanwhile, the role of PAD in achieving Gross Regional Domestic Product (GDP) is also still relatively low, reflected in the elasticity of GRDP to PAD which is still inelastic at around 0.8. This implies that the optimization of Regional Original Income (PAD) as the main source of revenue in self-financing government activities, development and services to the community is still quite low. Of course, this condition can have an impact on fiscal stress and is homework for the Maluku Provincial Government to further empower regional revenue sources.